Correlation study of climate variability, population density, altitude, and low birth-weight rates on the incidence of children pneumonia in Bogor Regency - Ariani; Arminsih, Ririn (Universitas Gadjah Mada, 2024)
Purpose: This study aims to analyze the correlation between climate variability (temperature, humidity, rainfall, sunshine duration, and wind speed), population density, altitude, and low birth weight (LBW) rate on the incidence of under-five years old children with pneumonia. Methods: This research uses a combination study design based on place and time (mixed design ecological study). Results: There was no significant relationship between climate variability and lag effect of 0-2 months with the number of under-five pneumonia cases in Bogor Regency in 2018-2022, as well as the altitude variable (p=0.0619). Meanwhile, the variables of population density (r-value = 0.439) and LBW rate (r-value = 0.338) showed a positive correlation with the number of under-five pneumonia cases in Bogor Regency. Conclusion: This research shows the incidence of pneumonia among under-fives in Bogor Regency is influenced by population density and LBW rates. Ensuring access to proper sanitation, a complete basic immunization program, adequate housing, and also personal protective measures are important to reduce the spread of pneumonia.